2020
DOI: 10.1111/liv.14367
|View full text |Cite
|
Sign up to set email alerts
|

Optimal management of chronic hepatitis B patients receiving nucleos(t)ide analogues

Abstract: Management of chronic hepatitis B (CHB) is still considered a challenge in clinical practice. Patients must be carefully evaluated before starting therapy. This includes virology and laboratory assessments, an estimation of fibrosis by invasive and/or noninvasive methods, and an estimation of the risk of hepatocellular carcinoma (HCC). Nucleos(t)ide analogues (NAs) with a high barrier to resistance (tenofovir disoproxil fumarate [TDF], entecavir [ETV] and tenofovir alafenamide [TAF]) are the most frequently us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
0
7
1
1
Order By: Relevance
“…However, some reports indicate that TDF might lead to a higher incidence of AKI compared to ETV in CHB patients [28,29]. As AKI is common in ACLF [30], renal injury associated with TDF use has raised some concerns [31]. However, in this single-center study, we found that the use of TDF did not increase the risk of AKI within one month of treatment.…”
Section: Discussioncontrasting
confidence: 57%
“…However, some reports indicate that TDF might lead to a higher incidence of AKI compared to ETV in CHB patients [28,29]. As AKI is common in ACLF [30], renal injury associated with TDF use has raised some concerns [31]. However, in this single-center study, we found that the use of TDF did not increase the risk of AKI within one month of treatment.…”
Section: Discussioncontrasting
confidence: 57%
“…HBV infection remains a global health concern due to its high incidence and mortality rates. According to the estimates made by the World Health Organization (WHO) in 2016, there were ~292 million individuals infected with HBV worldwide (7). There is sufficient evidence to indicate that CHB is a major cause of liver failure and hepatocellular carcinoma (8,9).…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, antiviral treatment has been demonstrated to prevent cirrhosis, liver failure and HCC [6]. One third of the patients in our cohort were under antiviral treatment at the end of follow-up.…”
Section: Plos Onementioning
confidence: 92%
“…Clinical manifestations of chronic HBV infection are broad, ranging from minimal inflammatory activity and fibrosis to active hepatitis with progressive fibrosis, cirrhosis, decompensated liver disease and/or HCC. Sustained HBV replication and liver injury are well-known risk factors for the development of HCC and treatment with nucleos(t)ide analogues does not eliminate the risk of HCC [6]. Thus, new antiviral strategies targeting different steps of the viral life cycle and the host immune response are currently being pursued, with the aim to reach HBV cure [7].…”
Section: Introductionmentioning
confidence: 99%